2013
DOI: 10.1039/c3ra42455c
|View full text |Cite
|
Sign up to set email alerts
|

Activated carbons as green and effective catalysts for generation of reactive radicals in degradation of aqueous phenol

Abstract: Several activated carbons (ACs) were used as metal-free catalysts for degradation of a toxic organic compound, phenol, in the presence of different oxidants, H 2 O 2 , peroxydisulfate (PS) and peroxymonosulfate (PMS). It was found that ACs were effective in heterogeneous activation of PMS to produce sulfate radicals for degradation of phenol, much better than H 2 O 2 and PS. Particle size of AC significantly influenced AC activity, and powder AC was much more effective than granular AC. The complete phenol rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…8d) two strong peaks can be observed in the spectrum of used MMO both at acid and neutral pH. One is at 1040 cm À1 , which is corresponding to S-O stretching vibration [47,48], and the other one is assigned to aromatic ring C@C stretching vibration at 1500 cm À1 . In addition, several relatively weak bands at 2940, 1385, 1200 and 833 cm À1 are observed, which are due to C-H stretching vibration, C-O stretching vibration and C-H out-plane bending vibration, respectively.…”
Section: Recycling Lifetime and Reactivation Ability Of Catalystmentioning
confidence: 90%
“…8d) two strong peaks can be observed in the spectrum of used MMO both at acid and neutral pH. One is at 1040 cm À1 , which is corresponding to S-O stretching vibration [47,48], and the other one is assigned to aromatic ring C@C stretching vibration at 1500 cm À1 . In addition, several relatively weak bands at 2940, 1385, 1200 and 833 cm À1 are observed, which are due to C-H stretching vibration, C-O stretching vibration and C-H out-plane bending vibration, respectively.…”
Section: Recycling Lifetime and Reactivation Ability Of Catalystmentioning
confidence: 90%
“…Complete phenol removal was achieved in 40 min on 3D hexagonally-ordered mesoporous carbon (CMK-3), while the reaction time for complete phenol decomposition was 210 min on cubically ordered mesoporous carbon (CMK-8). It has been reported that an activated carbon shows a similar activity [53].…”
Section: Adsorption Performance Of Nanocarbonsmentioning
confidence: 95%
“…It was worth noticing that the activation of persulfate by various carbonaceous materials, such as activated carbon [18], reduced graphene oxide (rGO) [19][20][21][22][23], carbon nanotubes (CNTs) [24][25][26][27][28], ordered mesoporous carbon (OMC) [29] and nanodiamond [30,31], had attracted much attention because of their environmental-friendly and high efficiency. Due to its high surface area, accessible mesopores and large pore volume, OMC had been applied in many areas such as adsorbents [32], catalysts and supports [33,34], and electrode materials [35].…”
Section: Introductionmentioning
confidence: 99%